Nitro-Oleic Acid Inhibits Stemness Maintenance and Enhances Neural Differentiation of Mouse Embryonic Stem Cells via STAT3 Signaling - Pereckova, Jana; Pekarova, Michaela; Szamecova, Nikoletta; Hoferova, Zuzana; Kamarytova, Kristyna; Falk, Martin; Perecko, Tomas (International journal of molecular sciences, 2021)
Nitro-oleic acid (NO2-OA), pluripotent cell-signaling mediator, was recently described as a modulator of the signal transducer and activator of transcription 3 (STAT3) activity. In our study, we discovered new aspects of NO2-OA involvement in the regulation of stem cell pluripotency and differentiation. Murine embryonic stem cells (mESC) or mESC-derived embryoid bodies (EBs) were exposed to NO2-OA or oleic acid (OA) for selected time periods. Our results showed that NO2-OA but not OA caused the loss of pluripotency of mESC cultivated in leukemia inhibitory factor (LIF) rich medium via the decrease of pluripotency markers (NANOG, sex-determining region Y-box 1 transcription factor (SOX2), and octamer-binding transcription factor 4 (OCT4)). The effects of NO2-OA on mESC correlated with reduced phosphorylation of STAT3. Subsequent differentiation led to an increase of the ectodermal marker orthodenticle homolog 2 (Otx2). Similarly, treatment of mESC-derived EBs by NO2-OA resulted in the up-regulation of both neural markers Nestin and β-Tubulin class III (Tubb3). Interestingly, the expression of cardiac-specific genes and beating of EBs were significantly decreased. In conclusion, NO2-OA is able to modulate pluripotency of mESC via the regulation of STAT3 phosphorylation. Further, it attenuates cardiac differentiation on the one hand, and on the other hand, it directs mESC into neural fate.
Keywords: Neurons; kyseliny olejové; signální transdukce; organogeneze; Cell Differentiation; pluripotentní kmenové buňky; transkripční faktor STAT3; Oleic Acids; pluripotency; Signal Transduction; myší embryonální kmenové buňky; Embryoid Bodies; cardiomyogenesis; Mice; mouse embryonic stem cells; Myocytes, Cardiac; neurogenesis; STAT3; zvířata; biologické markery; embryoidní tělíska; neurony; Pluripotent Stem Cells; STAT3 Transcription Factor; myši; Mouse Embryonic Stem Cells; nitro-oleic acid; kardiomyocyty; buněčná diferenciace; Organogenesis; Biomarkers; Nitro Compounds; dusíkaté sloučeniny; Animals